"Autopsychography" as a Form of Self-Narrative Inquiry. (November 2019) - Yuan, Yanyue; Hickman, Richard
In this article, we propose "autopsychography" as a form of self-narrative inquiry. Autopsychography seeks to track the shaping of creative paths when reflecting on lived experience as opposed to simply reporting what happened . We illustrate three major theoretical implications underpinning this concept: its rootedness in humanistic psychology that frames the human subject as the "whole person"; its emphasis on "change" and "growth, " core to educative experience; and its arts-informed features. We situate our discussions of autopsychography in the context of self-narrative approaches and we underscore its distinctiveness through comparisons with autoethnography as an already well-recognized methodology. We then present an autopsychographic study into Yanyue's experience after submitting the softbound copy of her PhD thesis in which she experimented with an "oral diary" and the use of "found poetry" as ways of presenting data.